Carte spéciale, historique et géographique de la République des États-Unis de l'Amérique du Nord. - Hacq, J. M. (Chez Paul Renouard, 1837)
Map shows the eastern United States, Florida Territory, and western territories to the Pacific coast as the Missouri, Arkansas, and Northwest Territories; the Republique du Mexique inclusive of [modern-day] Texas; areas of Native American habitation, treaty boundaries, and major cities. Includes notes, text, and statistics in left, right, and lower panels. Relief shown pictorially. Scale [ca. 1:15,000,000].